Tailoring metal-organic frameworks-based nanozymes for bacterial theranostics. (August 2021) - Ali, Arbab; Ovais, Muhammad; Zhou, Huige; Rui, Yukui; Chen, Chunying
Abstract: Nanozymes are next-generation artificial enzymes having distinguished features such as cost-effective, enhanced surface area, and high stability. However, limited selectivity and moderate activity of nanozymes in the biochemical environment hindered their usage and encouraged researchers to seek alternative catalytic materials. Recently, metal-organic frameworks (MOFs) characterized by distinct crystalline porous structures with large surface area, tunable pores, and uniformly dispersed active sites emerged, that filled the gap between natural enzymes and nanozymes. Moreover, by selecting suitable metal ions and organic linkers, MOFs can be designed for effective bacterial theranostics. In this review, we briefly presented the design and fabrication of MOFs. Then, we demonstrated the applications of MOFs in bacterial theranostics and their safety considerations. Finally, we proposed the major obstacles and opportunities for further development in research on the interface of nanozymes and MOFs. We expect that MOFs based nanozymes with unique physicochemical and intrinsic enzyme-mimicking properties will gain broad interest in both fundamental research and biomedical applications.